Septins From Protists to People - Shuman, Brent; Momany, Michelle (Frontiers in Cell and Developmental Biology, 2022)
Septin GTPases form nonpolar heteropolymers that play important roles in cytokinesis and other cellular processes. The ability to form heteropolymers appears to be critical to many septin functions and to have been a major driver of the high conservation of many septin domains. Septins fall into five orthologous groups. Members of Groups 1–4 interact with each other to form heterooligomers and are known as the “core septins.” Representative core septins are present in all fungi and animals so far examined and show positional orthology with monomer location in the heteropolymer conserved within groups. In contrast, members of Group 5 are not part of canonical heteropolymers and appear to interact only transiently, if at all, with core septins. Group 5 septins have a spotty distribution, having been identified in specific fungi, ciliates, chlorophyte algae, and brown algae. In this review we compare the septins from nine well-studied model organisms that span the tree of life (Homo sapiens, Drosophila melanogaster, Schistosoma mansoni, Caenorhabditis elegans, Saccharomyces cerevisiae, Aspergillus nidulans, Magnaporthe oryzae, Tetrahymena thermophila, and Chlamydomonas reinhardtii). We focus on classification, evolutionary relationships, conserved motifs, interfaces between monomers, and positional orthology within heteropolymers. Understanding the relationships of septins across kingdoms can give new insight into their functions.